2018
DOI: 10.20517/2394-4722.2018.12
|View full text |Cite
|
Sign up to set email alerts
|

Secondary malignancy estimation in patients after mastectomy and adjuvant therapy

Abstract: Aim: Secondary malignancy estimation after radiotherapy of post mastectomy patients is becoming an important subject for comparative treatment planning. The data from modern treatment planning systems provide accurate three-dimensional dose distributions for each individual patients, thereby opening up new possibilities for more precise estimates of secondary cancer incidence rates in the irradiated organs. Methods: This study estimates the probability of secondary malignancy using radiobiological model for po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Moreover, previous studies have suggested that breast cancer treatment could play a crucial role in the development of other primary malignancies as a late effect and consequence of the treatment [5,11]. Furthermore, SPC is one of the most serious and life-threatening adverse effects following radiotherapy, experienced by the growing number of cancer survivors worldwide, according to multiple studies, with a particular interest for postmenopausal women [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies have suggested that breast cancer treatment could play a crucial role in the development of other primary malignancies as a late effect and consequence of the treatment [5,11]. Furthermore, SPC is one of the most serious and life-threatening adverse effects following radiotherapy, experienced by the growing number of cancer survivors worldwide, according to multiple studies, with a particular interest for postmenopausal women [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%